Terfezia Boudieri and Terfezia Claveryi Inhibit the LPS/IFN-γ-Mediated Inflammation in RAW 264.7 Macrophages Through an Nrf2-Independent Mechanism - Dawood, Abdelhameed (AUC Knowledge Fountain, 2023)
Desert truffles have been used as traditional treatments for a variety of inflammatory disorders. However, the molecular mechanisms underlying their anti-inflammatory effects in RAW 264.7 macrophages have remained to be fully elucidated. Therefore, the present study investigated the anti-inflammatory activities of two main desert truffles, Terfezia boudieri and Terfezia claveryi and the underlying mechanisms associated with their anti-inflammatory activities in RAW 264.7 macrophages stimulated with lipopolysaccharide/interferon-gamma (LPS/IFN-γ) in order to develop innovative therapeutics for the treatment of inflammation. To address this objective, RAW 264.7 cells were treated with increasing concentrations of T. boudieri and T. claveryi extracts in the presence or absence of LPS/IFN-γ to determine the non-cytotoxic concentrations to be used in the study using MTT assay. RAW 264.7 cells were then stimulated with 100 ng/mL of LPS plus 10 U/mL of IFN-γ and co-incubated with T. boudieri and T. claveryi extracts at concentrations of 5, 10, and 20 µg/mL. Thereafter, the nitric oxide (NO) was measured using Griess assay. Quantitative real-time polymerase chain reaction (qPCR) was used to measure the mRNA expression levels of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), heme oxygenase-1 (HO-1), oxidative stress-induced growth inhibitor-1 (OSGIN1), and the microRNA expression levels of miR-21, miR-146a, and miR-155. On the protein level, enzyme-linked immunosorbent assay (ELISA) was used to determine the concentration of TNF-α and IL-6 proteins secreted into the cell culture supernatant, while western blotting was used to determine the protein expression of iNOS and COX-2. Our results demonstrated that LPS/IFN-γ significantly upregulated the mRNA expression of iNOS, COX-2, TNF-α, and IL-6. The production of NO, TNF-α, and IL-6 was remarkably increased in the medium of LPS/IFN-γ-treated RAW 264.7 cells. Moreover, the expression levels of miR-21, miR-146a, and miR-155 was induced in response to LPS/IFN-γ stimulation. The protein expression levels of iNOS and COX-2 were also increased in LPS/IFN-γ-activated RAW 264.7 cells. However, treatment with T. boudieri and T. claveryi extracts suppressed NO production in a concentration-dependent manner that coincided with downregulation of iNOS expression at the mRNA and protein levels in LPS/IFN-γ-stimulated RAW 264.7 cells. Both extracts also downregulated the mRNA expression of COX-2, but only T. boudieri which reduced the expression of COX-2 protein. On the level of pro-inflammatory cytokines, T. boudieri extract downregulated the expression of TNF-α and IL-6, as evidenced by dose-dependent reductions in their mRNA and protein levels. On the other hand, T. claveryi exhibited a significant inhibitory effect on the mRNA expression of TNF-α and IL-6 as well as the inhibition of TNF-α protein secretion. However, this effect failed to extend to the protein level of IL-6. Moreover, both studied extracts significantly downregulated the miRNA expression levels of miR-21, miR-146a, and miR-155, which implies that T. boudieri and T. claveryi suppress the inflammatory response in LPS/IFN-γ-stimulated RAW 264.7 cells through an epigenetic mechanism. To determine whether the anti-inflammatory effects of both Terfezia extracts in LPS/IFN-γ-induced RAW 264.7 cells were related to modulation of the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, we examined the potential effect of T. boudieri and T. claveryi on the Nrf2 target genes, HO-1 and OSGIN1. Our findings revealed that both extracts did not activate the Nrf2 target genes, suggesting that Terfezia-mediated anti-inflammatory properties are independent of Nrf2 pathway. Therefore, these results indicate that T. boudieri and T. claveryi exhibit anti-inflammatory activities through suppressing multiple inflammatory mediators and cytokines and may be potential anti-inflammatory agents.